Disaster Management in China in a Changing Era - Kang, Yi (Springer, 2015)
This book shows how Chinese officials have responded to popular and international pressure, while at the same time seeking to preserve their own careers, in the context of disaster management. Using the 2008 Wenchuan earthquake as a case study, it illustrates how authoritarian regimes are creating new governance mechanisms in response to the changing global environment and what challenges they are confronted with in the process. The book examines both the immediate and long-term effects of a major disaster on China’s policy, institutions, and governing practices, and seeks to explain which factors lead to hasty and poorly conceived reconstruction efforts, which in turn reproduce the very same conditions of vulnerability or expose communities to new risks. In short, it tells a “political” story of how intra-governmental interactions, state-society relations, and international engagement can shape the processes and outcomes of recovery and reconstruction.